Anatomi Transformasi: Studi Kasus Peran Agen dalam Pemberdayaan Masyarakat Desa Wisata Pujon Kidul, Malang - Mujtabah, Muhammad (Brawijaya University, 2024)
This study investigates the specific roles of agents in the development of a tourism village, using a single-case qualitative approach centered on Pujon Kidul Village, Malang. Data were collected through in-depth interviews with key informants, direct observations, and related document, and subsequently analyzed using a thematic analysis method. The findings reveal that agents play a central and multifaceted role in facilitating community empowerment. These roles include initiating and mobilizing social capital, fostering relationships and access to resources, acting as catalysts with adaptive and innovative habitus, and serving as strategic actors driven by strong motivation, expansive networks, and the capacity to overcome challenges. The study concludes that agents, shaped by a habitus grounded in both professional experience and local cultural values, are instrumental in mobilizing social capital and other resources to initiate and lead the village’s transformative development.